A Two-Year Retrospective Evaluation of Cone Beam Computed Tomography Indications in Pediatric, Adolescent and Adult Patients - Arslan, Zeynep Betül; Tuğutlu, Esra Ceren (Journal of Dentistry Indonesia, 2023)
Objective: The objective was to evaluate cone-beam computed tomography (CBCT) indications and distribution in pediatric, adolescent and adult patients. Methods: A total of 1013 CBCT images were reviewed in detail from the electronic patient database. The patient’s age, gender, CBCT indications and acquisition sites, referral departments, reason for referral, incidental findings in the imaging field and the presence of artifacts in the CBCT images were all recorded. The European DIMITRA project recommendations were used to categorize CBCT indications in the children and the European Guidelines were used for adults. Results: From a total of 1013 images; 5.3% were from children, 9.2% were from adolescents and 85.5% from were adult patients. The most common indication was impacted permanent teeth in children (37%) and adolescents (34%) and impacted 3rd molars (28.7%) and implant dentistry (25.8%) in adults. While the most common regional image was taken from children (37%) and adolescents (43.4%), it was determined that CBCT was taken from the maxilla+mandible (37.7%) in adults. Conclusion: Our results show that while attention was paid to use CBCT in children and adolescents in accordance with clinical guidelines and taking into account radiation protection protocols, it was used in the adult patient group in cases where it is not superior to traditional methods.